2011
DOI: 10.1039/c1ib00002k
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput combinatorial cell co-culture using microfluidics

Abstract: Co-culture strategies are foundational in cell biology. These systems, which serve as mimics of in vivo tissue niches, are typically poorly defined in terms of cell ratios, local cues and supportive cell-cell interactions. In the stem cell niche, the ability to screen cell-cell interactions and identify local supportive microenvironments has a broad range of applications in transplantation, tissue engineering and wound healing. We present a microfluidic platform for the high-throughput generation of hydrogel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
179
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(182 citation statements)
references
References 45 publications
1
179
0
2
Order By: Relevance
“…We assume that the cell viability increases with the cell density due to intensified paracrine signaling: 54,55 Since the mobility of rhodamine 6G as a model molecule is reduced by the presence of the microgel matrix, we expect that other, similarly sized molecules such as growth factors, which regulate cell survival and proliferation, may also exhibit a reduced mobility as compared to that in a nongelly environment. A higher cell density may thus compensate for this reduced mobility and allow cells to chemically communicate more easily.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We assume that the cell viability increases with the cell density due to intensified paracrine signaling: 54,55 Since the mobility of rhodamine 6G as a model molecule is reduced by the presence of the microgel matrix, we expect that other, similarly sized molecules such as growth factors, which regulate cell survival and proliferation, may also exhibit a reduced mobility as compared to that in a nongelly environment. A higher cell density may thus compensate for this reduced mobility and allow cells to chemically communicate more easily.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Kumachev et al (2011) showed a T-junction microfluidic device used for generation cell encapsulated agarose micro-beads with variable elasticity. Tumarkin et al (2011) presented a microfluidic platform for the high-throughput generation of hydrogel micro-beads for cell co-culture. These researches have revealed the potential of droplet-based microfluidics for preparation of agarose microgels in subsequent biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…6 For example, hydrogel microdroplets have been used as a building block for macroscale tissue generation 7 and a high-throughput platform for co-culturing cells. 8 Among several microdroplet fabrication methods, the most widely used method is the microfluidics-based method due to its high controllability of droplets, high throughput, low fabrication cost, and relatively simple device fabrication process. 9 There are three different methods to continuously generate microdroplets using the microfluidic devices: T-junction, flow-focusing, and co-axial flow methods.…”
Section: Introductionmentioning
confidence: 99%
“…The diameter of droplets is a key indicator of the size of droplets and has been widely used to characterize droplet generation mechanism. 8,10,14,15,19 The two most common methods to measure the diameter of droplets are optical sensing and electrical sensing. The electrical sensing is a low-cost, scalable method and uses the electrical property difference between aqueous and oil phase to detect the diameter of droplets.…”
Section: Introductionmentioning
confidence: 99%